Diversity of blood parameters of Oryctolagus cuniculus var. domestica L. reared in different ecological regions of Zarafshan oasis, Uzbekistan - DAVRON KHAYITOV; ZAYNITDIN RAJAMURADOV; BAXRITDIN BAZAROV; MIRZOXID KUZIEV; MARKHAMAT ISMAYILOVA; NATALYA ALLANAZAROVA; SHARIFKUL AMINJONOV; OYSОRA TОJIKULOVA; NIGORA RAKHMATOVA; DILNOZA NAMAZOVA; MUZAFFARA NORMURODOVA; MIRZAAHMAD KHUJABEKOV; DILOVAR KHAYDAROV; NURNISO RAJAMURADOVA (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Khayitov D, Rajamuradov Z, Bazarov B, Kuziev M, Ismayilova M, Allanazarova N, Aminjonov S, T?jikulova O, Rakhmatova N, Namazova D, Normurodova M, Khujabekov M, Khaydarov D, Rajamuradova N. 2024. Diversity of blood parameters of Oryctolagus cuniculus L. var. domestica reared in different ecological regions of Zarafshan oasis, Uzbekistan. Biodiversitas 25: 1465-1471. In the last 30 years, there has been a trend of rapid pollution of the atmosphere under the influence of climate change, urbanization and anthropogenic factors. According to statistics, the quality of the products obtained from agricultural animals deteriorates under the influence of the above-mentioned stress factors in some regions of Uzbekistan, and the number of livestock decreases annually by 1.8-2.3%. In this regard, there is an increasing need to research the effects of extreme climate and abiotic factors on rabbits' physiological state and biochemical indicators to effectively maintain agricultural animals, including rabbits, in extreme conditions and increase their productivity. This study is one of the first studies of this type, aimed at determining the blood parameters of the Chinchilla breed of rabbit - Oryctolagus cuniculus var. domestica L., raised in the ecological regions of Zarafshan oasis (Uzbekistan) with different air temperatures, rainfall, and atmospheric pollution. The lack of information in scientific sources on the variability of blood parameters in rabbits raised in different ecological regions due to changes in climate indicators and atmospheric air pollution indicates that in-depth research has not been conducted in this regard. According to the results of the research, rearing in ecological regions with different air temperatures, rainfall, and atmospheric pollution has a direct effect on the number of erythrocytes, leukocytes, and hemoglobin in the blood of rabbits, the composition of blood proteins, and indicators of cellular and humoral immunity in the blood. Changes in these indicators are observed by environmental pollution. The information presented in the article serves to explain the diversity of blood parameters in O. cuniculus, kept in different ecological environments, and to choose the right approach for feeding rabbits.